Bibliometric Analysis of English for Specific Purposes Between 1991-2023 with Particular Focus on the Importance of Vocabulary - Saidova, Zulfizar; Zakirova, Khilola; Ilangovan, Ajit; Nodira, Atabayeva; Zaruxan, Utemuratova; Mokhira, Mavlanova; Nazokat, Sabirova; Kannazarova, Zulfiya (Forum for Linguistic Studies, 2025)
ESP (English for Specific Purposes) primarily serves for EFL-English as a foreign language speakers in academic and professional contexts, where vocabulary plays a significant role in learning, teaching, and researching specialized forms of the English language. This paper presents a comprehensive review to understand research trends in this area. The aim is to analyze scientific output and published articles on ESP vocabulary from 1991 to 2023. To achieve this, we collected, reviewed, and analyzed 279 publications. Annual number of articles, document type, top articles, top journals, funding sponsors, subject categories and journals, distribution, and institutional affiliation by country categorized these publications. This study maps the knowledge area objectively and aims to identify the status, major research themes, evolution, and emerging trends in this field. This classification helps assess their relevance and the co-occurrence of co-authors and keywords. The current research status through publication distribution and co-country network shows that the research is undergoing a steady increase in international authorship. The bibliometric analysis in the article brings out intellectual interactions, thematic strengths, and the evolving interests of various focus groups using scientific methods. In addition, the paper suggests emphasizing international research on ESP vocabulary to enhance scientific exchange and promote long-term, sustainable development in this sphere. As the ESP field continues to experience exponential growth and development, it indicates an ongoing expansion and advancement of research in this area. This research provides references for researchers to understand the status, hidden structure, evolution, and emerging future direction of research trends in ESP.